LEGAL REVIEW ON THE LEGITIMACY OF GUARDIAN TO THE MARRIAGE OF ADOPTED CHILD - Ani Yumarni (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACT               A legal marriage is the process of marriage which qualifies the requirements and pillars stipulated by law. However, the appearance of consenting marital guardian (wali) of marriage is among the pillars of legitimate (rukun) marriage. Accordingly, guardian as mentioned here is a relative guardian. This stipulation is applied to daughters including adopted daughters who intentionally going to perform marriage. In particular condition in the society, sometimes, a marital guardian of adopted daughters is untraceable.  Therefore, in order to examine and analyze the legitimate person to be guardian of marriage, an appropriate legal remedy that becomes the purpose of this research is needed. The methodology applied in the research is juridical normative approach whereby objectively explaining particular data followed by an analysis based on legal theory and related statutes of research objects. However, the custodial right of adopted child is only restricted to the right of custody, nurture, and education. On the other hand, marital custodial right is still belongs to biological parent so long the family tree is identifiable. On the contrary, In case of biological marital guardian is unidentifiable, a guardian judge can perform such right according to the court decision. It was advocated by Article 49 of Law No. 3 of 2006 concerning on Shariah Court. At the same vein, article 17 stipulated on the appointment of another person as guardian in case of somebody’s custodial right is rejected, and followed by Article 18 which stipulated on the appointment of guardian of not 18 (eighteen) years old enough bereaved child. Keywords: Guardian, Marriage, Adopted child.